2008
DOI: 10.1111/j.1365-2141.2008.07024.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐CD20 monoclonal antibody therapy in multiple myeloma

Abstract: SummaryCD20 is a particularly appealing target that is expressed on the surface of almost all B cells, with no significant shedding, secretion or internalization. In contrast to the demonstrated efficacy of anti-CD20 strategies in various B-cell lymphoproliferative disorders, the role of such therapy in multiple myeloma is undetermined and controversial. The expression of CD20 by myeloma cells is heterogeneous, and can be detected only in 13-22% of patients. However, there is increasing interest in testing ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 113 publications
3
81
0
2
Order By: Relevance
“…However, not all CD20 1 patients respond to rituximab; in fact, only 10% of the CD20 1 patients are responsive. 35 In this paper, we demonstrated that the expression of the complement regulator CD59 is associated with resistance to rituximab-mediated complement lysis in the ARH-77 MM cell line. rILYd4 was effective in abrogating the function of hCD59 in the ARH-77 cell lines.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, not all CD20 1 patients respond to rituximab; in fact, only 10% of the CD20 1 patients are responsive. 35 In this paper, we demonstrated that the expression of the complement regulator CD59 is associated with resistance to rituximab-mediated complement lysis in the ARH-77 MM cell line. rILYd4 was effective in abrogating the function of hCD59 in the ARH-77 cell lines.…”
Section: Discussionmentioning
confidence: 78%
“…35 Recent studies are indicative of the existence of clonogenic CD20-positive precursor B cells in myeloma; thus there is increasing interest in testing anti-CD20 therapies in the disease. 35 In order to test whether rILYd4 enhances the rituximab-mediated CDC effect on MM cells, we used FACS analysis to detect CD20-positive and CD59-postive ARH-77 cells and human MM cells (Figure 2a). We demonstrated that rILYd4 sensitized ARH-77 cells to the CDC effect mediated by rituximab (20 mg/ml) in a dose-dependent manner (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…(95)(96)(97) In the last decade, MFC immunophenotypic characterization of phenotypically aberrant PC has also been suggested to be a valuable tool for the detection of potential therapeutical targets on clonal PC and orientate tailored antibody-based therapies (and subsequent monitoring). Thus, MoAbs targeting the overall PC population (CD138) (98,99) or either growth factor receptors (IL-6 or IGF-1) (100,101) and other cell surface antigens expressed by aberrant PC (CD33, CD40, CD52, or CD74) (102)(103)(104)(105)(106)(107) and specific markers whose expression is restricted to subsets of PC (e.g. CD19, CD20, CD27, or CD117) have been developed and, several of them are currently under evaluation in phase I/II clinical trials (70,71).…”
Section: Utility Of Mfc In MM and Other Plasma Cell Dyscrasiasmentioning
confidence: 99%
“…[16]. [18]. Aufgrund der geringen CD20-Expression bei MM-Zellen ist der therapeutische Nutzen aber allenfalls minimal in ausgewählten Fällen.…”
Section: Einfluss Der Therapieunclassified